Mathematical Model for Population Growth. Case Study: Ethiopia - Souksomvang, Phoui (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this paper is to use mathematical models to predict the population growth of Ethiopia. Ethiopia is an overpopulated country in Africa next to Nigeria. It shares a border with Eritrea to the North and Northeast, Djibouti and Somalia to the East, Sudan and South Sudan to the West, and Kenya to the South. The Malthus’s and the logistic growth models are applied to model the population growth of Ethiopia using data from 1980 to 2020. The data used was collected from International Data Base (IDB). We also use the least square method to compute the best population growth rate of Malthus’s model. The Malthus’s population model predicted a growth rate of 2.9% per year while the logistic growth model predicted the carrying capacity of and growth rate of 2.9% per annum. The growth rate for both models match well with the growth rate estimated by International Data Base for the past four years. The Mean Absolute Percentage Error is computed as 0.62% for Malthus’s population model and 0.64% for logistic growth Model. This showed that the Malthus’s population model seems to fit the original data the best among the models we tried.